2002
DOI: 10.1016/s0002-9440(10)61167-4
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin/Heparin-Binding Growth-Associated Molecule as a Mitogen of Rat Hepatocytes and Its Role in Regeneration and Development of Liver

Abstract: Previously pleiotrophin (PTN) was identified among proteins secreted by Swiss 3T3 cells as a mitogen for cultured adult rat hepatocytes. The present study showed that the growth of rat hepatocytes was enhanced when cultured with rat hepatic stellate cells (HSCs). HSCs expressed PTN mRNA and secreted its protein in the co-cultures. Recombinant PTN enhanced the growth of hepatocytes in culture, suggesting that HSCs stimulate the growth of hepatocytes through the action of PTN. To know the biological role of PTN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 45 publications
5
75
0
4
Order By: Relevance
“…Especially the role of HSCs in the hepatic fibrogenesis and carcinogenesis has been a major issue among investigators [32]. Previously, we showed that HSCderived PTN plays a role as a hepatocytes growth factor [6,9]. Furthermore, we showed that PTN expression was increased in CCl 4 -induced fibrotic liver [10], suggesting the involvement of PTN in hepatic fibrogenesis, to which TGFb1 is also committed as an anti-hepatocyte growth factor and an ECMformation accelerator.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Especially the role of HSCs in the hepatic fibrogenesis and carcinogenesis has been a major issue among investigators [32]. Previously, we showed that HSCderived PTN plays a role as a hepatocytes growth factor [6,9]. Furthermore, we showed that PTN expression was increased in CCl 4 -induced fibrotic liver [10], suggesting the involvement of PTN in hepatic fibrogenesis, to which TGFb1 is also committed as an anti-hepatocyte growth factor and an ECMformation accelerator.…”
Section: Discussionmentioning
confidence: 97%
“…PTN is an 18 kDa heparin binding protein and shows 50% identity to midkine (MK) [2][3][4]. It promotes the growth of fibroblasts, endothelial cells, and hepatocytes [4][5][6]. Its gene is grouped as a potent proto-oncogene [7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditional cell lineage tracing using Wt1 CreERT2 ; Rosa26 flox (R26 f ) reporter mice demonstrated that the Wt1 + mesothelium migrates inward from the liver surface and gives rise to hepatic stellate cells (HSCs), fibroblasts, and smooth muscle cells during liver morphogenesis (8). In addition, embryonic MCs may support proliferation of hepatoblasts by secretion of hepatocyte growth factor (HGF) and pleiotrophin (PTN) (9,10). These results indicate that MCs are progenitor cells of liver mesenchymal cells and play a role in hepatogenesis.…”
mentioning
confidence: 99%
“…The influence of liver regeneration, especially regeneration after partial hepatectomy, on other functions of HSCs has been examined from various aspects. For example, the start point of DNA synthesis of HSCs (Tanaka et al, 1990); alterations in the amounts of protein products, including cytokines, enzymes, and transcription factors (Marsden et al, 1992;Watanabe et al, 1998;Ujiki et al, 2000;Asahina et al, 2002); and cell-cell interactions between HSCs and hepatocytes (Mabuchi et al, 2004) have been already assessed in the regenerating liver after 70% PHx. The fact that hepatocyte-HSC interaction in the early stages after PHx (1-3 days) is intimately involved in the regeneration process (Mabuchi et al, 2004) has particularly shown the importance of the role of HSCs during liver regeneration (Balabaud et al, 2004).…”
mentioning
confidence: 99%